EFEKTIFITAS PENGGUNAAN E-LEARNING BERBASIS OPEN SOURCE PADA PEMBELAJARAN JARAK JAUH SMP IT DI KABUPATEN BEKASI - Acep Musliman; Mamik Suendarti (AKSELERASI: Jurnal Ilmiah Nasional, 2021)
When the globe was engulfed by the COVID-19 pandemic, substantial adjustments were undertaken in the educational system. Face-to-face learning is prohibited by the government in order to prevent the spread of this illness. Since the epidemic, distance learning has emerged as a new learning technique for students. At SMPIT in Bekasi Regency, this project attempts to assess the efficacy of adopting Open source-based E-Learning in distant learning. Pre-test-post-test control group design is a quasi-experimental design used in this study to create the genuine experimental technique by treating the research subject in question with a particular treatment. As a result, the experimental group's post-test average value and normalized gain were higher than the control group. The experimental group's average value was 85.97 while the control group's average value was 80.19. The experimental group's normalized gain value was 0.52 while the control group was only 0.30.